การประเมินโครงการประกันคุณภาพภายในสถานศึกษาโรงเรียนวัดขนาบนาก สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษานครศรีธรรมราช เขต 3 - Choosuk, Rattiya; Nukaew , Sujin (Journal of Graduate School Sakon Nakhon Rajabhat University, 2023)
The purpose of this research was to assess school internal quality assurance programs of Watkanabnak School, in the academic year 2020, under Nakhon Si Thammarat Primary Educational Service Area Office 3, by applying the CIPP assessment model, regarding context, input, process, and product. The population consisted of 84 participants, which included six teachers, one school administrator, seven school board members, 35 students from Prathomsuksa 4 to 6, and 35 parents of the students. The tool for data collection consisted of four sets of 5-level scale questionnaires. The statistics used were percentage, mean, and standard deviation. The results were as follows: 1. The context was overall at a high level. The statement indicating that the projects addressed the needs of both students and parents received the highest mean score. 2. The input was overall at a high level. The statement indicating that administrators, teachers, and stakeholders gained knowledge and understanding in terms of internal quality assurance received the highest mean score. 3. The process was overall at a high level. The statement indicating that the persons in charge of the projects reported the internal quality assurance performance to the school administrators received the highest mean score. 4. The product was overall at a high level. The statement indicating that students were in a state of good physical and mental health received the highest mean score.